Effects of electronic markets on prices, spikes in prices, and price dispersion: A case study of the tea market in India - Pallavi Rajkhowa; Lukas Kornher (Agribusiness, 2023)
Buyers and sellers in developing countries are often restricted from accessing distant markets by asymmetric price information and costly searches. Electronic marketplaces can reduce transaction costs and improve market performance. This study uses monthly panel data from 2000 to 2017 and applies a fixed effects approach using Driscoll and Kraay standard errors to address spatial and temporal correlations to provide empirical evidence on the effects of electronic markets on prices, spikes in prices, and price dispersion of an agro-based commodity in India. The findings indicate that, between 2000 and 2017, the introduction of electronic markets reduced prices and short-term variability in tea prices by nearly 2%. Moreover, electronic markets initially increased price dispersion between markets by 11%–14%; however, with further reduction in market friction over time, price dispersion reduced by 16%.~[EconLit Citations: Q11, Q13].
Keywords: 630; agriculture; electronic marketplaces; ICTs; market efficiency; price dispersion